BIBLIOMETRIC ANALYSIS OF THE LITERATURE INDICATED IN THE BIBLIOGRAPHICAL REFERENCES OF THE PROGRAMS OF BASKETBALL SUBJECTS, IN THE COURSES OF PHYSICAL EDUCATION OF SANTA CATARINA (Fiep Bulletin - online, 2014)
Documentary research that it analyzed by bibliometriacs, the 237 different literature indicated in bibliographies of the programs of the discipline of basketball, in the superior courses of Physical Education of Santa Catarina. Specifically it was intended: It identified the more cited author; b) determined the average life of cited literature; c) it identified the boarded subjects, the language of the publication, the date of the publication, the number of authors and the bibliographical source of the enrolled literature. All the Institutions of Superior Education of the State of Santa Catarina had participated of the research that in 2004/2005 offered the Course of Graduation in Physical Education. The results had indicated that: ) the two authors had tied up to as more cited, ALMEIDA, M.B and DAIUTO, M. both with 18 (7.6%) of the indications; b) the average life of literature is of 10 years; c) the subject most boarded was the sport with 212 (89%) indications; d) the Portuguese is the indicated language more in literature; e) the oldest literature indicated date of the 1957 and most current one of 2003; f) the source or bibliographical support more used is the book printed matter. The results point little innovation in the programs of the discipline of basketball, the indicated authors repeat itself frequently, the most boarded approach from 1969 to 2003 is the sport (practical porting, game, beddings, rules…), the reading of literature in other languages is not common, the book printed matter continues being main the informational support of the area.
Keywords: Citation analysis; Bibliometrics; Basketball